2017
DOI: 10.15421/011707
|View full text |Cite
|
Sign up to set email alerts
|

Transformation in the diversity of avifauna under the influence of recreational load

Abstract: This article examines the bird community of a large reservoir and its surrounding area , located in the central part of a large city in the northern part of the steppe zone of Ukraine. The city, Krivoy Rog, has a population of over 700,000 people. Large areas of the city have undergone dramatic transformation. Industrial and and residential areas of the city are located around the reservoir. The shores of the reservoirs are subject to recreational loading. The natural landscape here is a combination of steppe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…An important factor affecting the number of birds is the degree of transformation of grassy and shrubby layers for ground birds (Camprodon, Brotons, 2006;Heyman, 2010;Shupova, 2017). Moreover, our results show that a stage of recreational transformation causes a marked decrease in the abundance of ground birds in all EP.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…An important factor affecting the number of birds is the degree of transformation of grassy and shrubby layers for ground birds (Camprodon, Brotons, 2006;Heyman, 2010;Shupova, 2017). Moreover, our results show that a stage of recreational transformation causes a marked decrease in the abundance of ground birds in all EP.…”
Section: Discussionmentioning
confidence: 60%
“…Studies of breeding birds are particularly relevant to create the dependencies between the transformation of phytocoenosis and avifauna. Specific features of breeding bird density distribution in urban forest reflected heterogeneity of their populations with respect to connections with nesting biotopes (Camprodon, Brotons, 2006;Shupova, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Trampling down leads to the transformation of the herbaceous cover, the destruction of shrubbery and the reduction in the proportion of birds ground nesters (Camprodon, Brotons, 2006;Heyman, 2010;Šalek et al, 2010). The authors showed that the dogs walking prevents the arrangement of nests and contributes to the reduction in the number of birds associated with the ground level (Shupova, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that habitat conditions of T. philomelos are crucial for the successful breeding and population stability of the species in forests of Germany (Batary et al, 2014), Sweden (Felton et al, 2016), Romania (Domokos & Domokos, 2016), Spain (Moreno-Rueda & Pizzaro, 2009), and for equivalent species in Southeast Asia (Hamer et al, 2015). This issue becomes especially urgent in the north-eastern part of Ukraine, characterised by the intensive transformation of natural communities (Brygadyrenko, 2014(Brygadyrenko, , 2015Shupova, 2017). Understanding of particular foraging characteristics of insectivorous birds is important to mitigate invasions of arthropods, which are potential carriers of diseases dangerous to humans (Anderson & Magnarelli, 1993;Lommano et al, 2014), as well as mitigate invasions of pests of forestry and agriculture (Faly & Brygadyrenko, 2014;Chaplygina et al, 2015;Caprio & Rolando, 2017).…”
Section: Introductionmentioning
confidence: 99%